Research of Milk-Protein Concentrates and Fruit Vegetable Puree Surface Activity in the Ice Cream Composition - Polishchuk, Galyna; Osmak (Fedchenko), Tetiana; Bandura (Kuzmyk), Uliana; Sapiga, Victoria; Mykhalevych, Artur (My University, 2019)
The purpose of the scientific paper is to study the surface activity of milk-protein concentrates and pectin-containing fruit-vegetable purees as functional and technological components in the composition of creamy ice cream. The surface activity of milk proteins and the surface neutrality of pectin-containing purees were confirmed. Synergism ofproteins and polysaccharides interaction for the formation of dispersed ice cream systems, in particular, milk fat emulsion, has been established. The conclusion about the important role of complex application of protein compounds exhibiting surface activity and polysaccharides that determine the structural and mechanical stability factor of dispersed ice cream systems is formulated. Мета наукової роботи - вивчити поверхневу активність молочно-білкових концентратів та пектиносодержащих фруктово-овочевих пюре як функціональних та технологічних компонентів у складі вершкового морозива. Підтверджено поверхневу активність молочних білків та поверхневу нейтральність пектиносодержащих пюре. Встановлено взаємодію взаємодії протеїнів та полісахаридів для утворення дисперсної системи морозива, зокрема, молочної жирової емульсії. Сформульовано висновок про важливу роль комплексного застосування білкових сполук, що виявляють поверхневу активність, та полісахаридів, що визначають фактор структурної та механічної стійкості дисперсних систем морозива.
Keywords: ice cream; морозиво; milk proteins; молочний білок; кафедра технології молока і молочних продуктів